European facilities for advanced accelerators development. (1st May 2022) - Muggli, P.; Ferrario, M.; Osterhoff, J.; Cros, B.
Abstract: Research on the application of advanced and novel accelerator schemes to high-energy physics requires facilities capable of producing multi-GeV particle beams. We briefly review the challenges faced by advanced accelerators in reaching collider-relevant parameters and give a concise description of relevant European facilities and large scale installations, either in operation or in a state of advanced design, with their main goals. We also emphasize contributions from smaller, mostly university groups or laboratories. These facilities and groups advance the field considerably and address some of the challenges arising in the translation of advanced accelerator concepts to a future high-energy physics machine. We highlight the fact that there is in addition the strong need for a dedicated European facility with a scientific and R&D program specific to the research questions exclusive to a plasma-based e - e + linear collider.